WS2: A New Window Layer Material for Solar Cell Application - Bin Rafiq M.K.S.; Amin N.; Alharbi H.F.; Luqman M.; Ayob A.; Alharthi Y.S.; Alharthi N.H.; Bais B.; Akhtaruzzaman M. (Nature Research, 2023)
Radiofrequency (RF) magnetron sputtering was used to deposit tungsten disulfide (WS2) thin films on top of soda lime glass substrates. The deposition power of RF magnetron sputtering varied at 50, 100, 150, 200, and 250 W to investigate the impact on film characteristics and determine the optimized conditions for suitable application in thin-film solar cells. Morphological, structural, and opto-electronic properties of as-grown films were investigated and analyzed for different deposition powers. All the WS2 films exhibited granular morphology and consisted of a rhombohedral phase with a strong preferential orientation toward the (101) crystal plane. Polycrystalline ultra-thin WS2 films with bandgap of 2.2 eV, carrier concentration of 1.01 1019 cm?3, and resistivity of 0.135 ?-cm were successfully achieved at RF deposition power of 200 W. The optimized WS2 thin film was successfully incorporated as a window layer for the first time in CdTe/WS2 solar cell. Initial investigations revealed that the newly incorporated WS2 window layer in CdTe solar cell demonstrated photovoltaic conversion efficiency of 1.2% with Voc of 379 mV, Jsc of 11.5 mA/cm2, and FF of 27.1%. This study paves the way for WS2 thin film as a potential window layer to be used in thin-film solar cells. 2020, The Author(s).